In Defense of Self-care - Fuller, Leanna K. (2018)
This article focuses on the concept of "self-care" in ministry. I begin by exploring contemporary critiques of self-care as self-indulgent and theologically inadequate. I contend that such critiques are based on an individualistic understanding of the self, which is inattentive to social location and obscures the relationship between self and community. Drawing on feminist, womanist, and pastoral theological resources, I argue for an approach to self-care that acknowledges differing experiences of selfhood and that recognizes the fundamental connection between personal and communal well-being. This approach lays the groundwork for a renewed focus on self-care as a pathway to life-giving ministry.
Keywords: Self-care; Clergy health; Feminist Theology; Ministry; Pastoral Care; Pastoral Theology; Self-sacrifice; Womanist Theology